Microbial Profile and Safety of Chicken Eggs from a Poultry Farm and Small-Scale Vendors in Hawassa, Southern Ethiopia - Abraham Damena; Abraham Mikru; Million Adane; Beyene Dobo (Journal of Food Quality)
A freshly laid hen’s egg is devoid of microorganism, but soon after oviposition, it is contaminated by various spoilage and pathogenic microorganisms. The aim of this study was to assess the microbial profile and safety of chicken eggs in Hawassa City. A total of 60 egg samples were collected from Hawassa University Poultry Farm (HUPF) and small-scale vendors in Hawassa. The samples were analyzed for aerobic mesophilic bacterial count (AMBC), Staphylococcal count (SC), Enterobacteriaceae count (EC), total coliform count (TCC), fecal coliform count (FCC), and yeast and mold count (YMC). Moreover, the dominant mesophilic aerobic bacterial genera and common bacterial pathogens were identified by phenotypic methods. Accordingly, the mean aerobic mesophilic bacterial load of the shell surface rinsate of the egg samples ranged from 1.22 log10 CFU/ml to 9.7 log10 CFU/ml, while that of the internal contents ranged from 1.52 log CFU/ml to 9.36 log CFU/ml. The microbial load values of the egg contents were beyond the international recommended acceptable limits and suggested incipient spoilage. The mesophilic aerobic bacterial genera of the shell and internal contents of the egg samples were similarly dominated by Pseudomonas, Micrococcus, and Staphylococcus. The incidence of E. coli in shell rinsate and egg content was 10% (6 of 60) and 1.67% (1 of 60), respectively. Salmonellae were detected in shell rinsate of six egg samples (10%) and in the contents of eight samples (13.33%), all from small-scale vendors. These findings call for vigilant exercise of good agricultural and hygienic practices by primary producers and retailers.